Efek Regulasi Emosi terhadap Kecemasan Prapertandingan Atlet UKM Tekwondo di Kota Makassar - Dewi Angreini; Nurul Khumaerah; Aswar (Psyche 165 Journal, 2021)
This study aims to determine the effect of emotion regulation on pre-match anxiety of Taekwondo UKM athletes in Makassar City. This study uses a quantitative approach. The population in this study was SME Taekwondo athletes in Makassar City totaling 100 people with a sample of 50 people. By analyzing the data using SPSS 23.0 for Windows to test normality and linearity, and to test the hypothesis with simple regression. The results of this study indicate the value of F = 11,978 with a significance of 0.003 (p<0.05) which indicates that emotional regulation has a significant effect on anxiety in dealing with competition in Taekwondo UKM athletes in Makassar City. While the value of R is 0.195, it shows that emotion regulation affects the athlete's anxiety. Based on these results, the research hypothesis is accepted.